High-performance two-ply yarn supercapacitors based on carbon nanotubes and polyaniline nanowire arrays - Wang, Kai (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.